A comparison of existing global DNA methylation assays to low-coverage whole-genome bisulfite sequencing for epidemiological studies. Issue 3 (4th March 2017) - Crary-Dooley, Florence K.; Tam, Mitchell E.; Dunaway, Keith W.; Hertz-Picciotto, Irva; Schmidt, Rebecca J.; LaSalle, Janine M.
ABSTRACT: DNA methylation is an epigenetic mark at the interface of genetic and environmental factors relevant to human disease. Quantitative assessments of global DNA methylation levels have therefore become important tools in epidemiology research, particularly for understanding effects of environmental exposures in complex diseases. Among the available methods of quantitative DNA methylation measurements, bisulfite sequencing is considered the gold standard, but whole-genome bisulfite sequencing (WGBS) has previously been considered too costly for epidemiology studies with high sample numbers. Pyrosequencing of repetitive sequences within bisulfite-treated DNA has been routinely used as a surrogate for global DNA methylation, but a comparison of pyrosequencing to WGBS for accuracy and reproducibility of methylation levels has not been performed. This study compared the global methylation levels measured from uniquely mappable (non-repetitive) WGBS sequences to pyrosequencing assays of several repeat sequences and repeat assay-matched WGBS data and determined uniquely mappable WGBS data to be the most reproducible and accurate measurement of global DNA methylation levels. We determined sources of variation in repetitive pyrosequencing assays to be PCR amplification bias, PCR primer selection bias in methylation levels of targeted sequences, and inherent variability in methylation levels of repeat sequences. Low-coverage, uniquely mappable WGBS showed the strongest correlation between replicates of all assays. By using multiplexing by indexed bar codes, the cost of WGBS can be lowered significantly to improve the accuracy of global DNA methylation assessments for human studies.